Assessing and predicting the need for Adaptive Radiotherapy in Head & Neck cancer patients - Alves, Natalia Bortolami Colaco (2020)
Trabalho de Projeto do Mestrado Integrado em Engenharia Biomédica apresentado à Faculdade de Ciências e Tecnologia